GAMBARAN PENGETAHUAN IBU HAMIL TENTANG HYPEREMESIS GRAVIDARUM DI WILAYAH KERJA PUSKESMAS BATANGTORU TAHUN 2024 - Mutia, Fatma; Harahap, Masnawati (Universitas Aufa Royhan, 2024)
Pregnancy can cause changes such as an increase in hormones, one of which is nausea and vomiting. Hyperemesis Gravidarum is excessive nausea and vomiting in pregnant women which causes activities to be disrupted and the mother's condition worsens. The purpose of this study was to determine the description of the knowledge of pregnant women about hyperemesis gravidarum in the Batangtoru Community Health Center Work Area in 2024. This type of research is quantitative with descriptive method. The population in this study were first trimester pregnant women in the Batangtoru Community Health Center Work Area as many as 31 people December 2023 - February 2024, and the number of samples in this study were 31 people using the total sampling method. The analysis used was univariate. The results of the analysis showed that the knowledge of pregnant women about hyperemesis gravidarum in less knowledge as many as 12 people (38.7%). It is recommended for pregnant women to be more active in seeking information to health workers so that mothers get counselling about hyperemesis gravidarum and the dangers that can be caused to mothers and children so as to increase the knowledge of pregnant women about hyperemesis gravidarum.